ANALISIS KOMPREHENSIF TERHADAP PENGELOLAAN KERJA DI KETINGGIAN PT. GALANGAN KARIMUN SEMBAWANG SESUAI DENGAN PERATURAN REPUBLIK INDONESIA - Trisno Susilo (JURNAL CAFETARIA, 2023)
Working at Height is very common activity in Shipyard. Working at Height is an activity which carried out by people or workers at least at 1.8 meters high from the ground floor or bottom. Working at height has several risks that could threaten the health of the workforce, including falls, being hit by material from above, hypoxia, decompression, sinusitis, visual disturbances, and mental and psychological disorders. Therefore, Managing Working at Height is very crucial and need a special attention from Top Management of the Company or Organization. PT. Karimun Sembawang Shipyard has a policy to manage the workforce which involve on Working at height to protect them from all the risk while they are working at height. The purpose of this research is to analyse the Management system on Working at Height adopted by PT. Karimun Sembawang Shipyard compere with Indonesian Regulation and the Expertise perspective. The Result of this research showing that the Management on Working at Height adopted by PT. Karimun Sembawang Shipyard is more stringent or above the Indonesian Regulation requirement as stated in Permenaker No.9 year 2016. Therefore it can be take as a sample for other companies to comply the similar policy on the Management of Working at Height.